2020
DOI: 10.3390/jcm9020592
|View full text |Cite
|
Sign up to set email alerts
|

Collaborating with Complementary and Alternative Medicine (CAM) Providers When Writing HPV Vaccine Review Articles

Abstract: Novel strategies are needed to address vaccine hesitancy (VH), which correlates with complementary and alternative medicine (CAM). In Switzerland, CAM providers play important roles in vaccine counseling of vaccine hesitant (VH) parents, and traditional vaccination messaging tends to overlook CAM provider perspectives. In the setting of a Swiss national research program on VH, our key strategy has been to work together closely with CAM providers. To assess the feasibility of generating educational human papill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Regarding HPV vaccine, many physicians, but few pharmacists and nurses, completely encouraged patients/clients to follow the official vaccination recommendations. This could be due to HCPs feeling uncomfortable addressing sexual topics ( 25 ) or HCPs being uncertain about the need for HPV vaccine ( 44 , 45 ). Another potential explanation is that pharmacists and nurses may be less familiar with the vaccination schedule for adolescents compared to physicians.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding HPV vaccine, many physicians, but few pharmacists and nurses, completely encouraged patients/clients to follow the official vaccination recommendations. This could be due to HCPs feeling uncomfortable addressing sexual topics ( 25 ) or HCPs being uncertain about the need for HPV vaccine ( 44 , 45 ). Another potential explanation is that pharmacists and nurses may be less familiar with the vaccination schedule for adolescents compared to physicians.…”
Section: Discussionmentioning
confidence: 99%
“…The use of CM and is common among 25%–50% of the population. Contrary to common preconceptions, CM providers are not categorically opposed to vaccination ( 25 ). Rather, research has shown how they prefer individualized, patient-centered vaccination counseling that addresses the pros and cons of vaccination, emphasizes the autonomy of parents in their medical decisions, and involves them in vaccination decisions ( 26 , 27 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although CAM literature cannot be simply described as being either pro-or antivaccination without considering finer areas of disagreement [45,46], CAM has emerged as part of an expert system countering conventional medicine, and pro-vaccination health professionals, policymakers, and information providers seeking to address the role of CAM in vaccine rejection face significant challenges due to the epistemic basis of its proponents' decisions [47]. Engaging with CAM providers appears to be a feasible and innovative avenue for providing vaccine information and designing communication tools aimed at vaccine-hesitant healthcare providers [48].…”
Section: Discussionmentioning
confidence: 99%
“…9 Our Swiss National Research Programme 74 (NRP74) on VH and underimmunisation focuses on both biomedical providers and providers of complementary and alternative medicine (CAM). [10][11][12] CAM is popular in many countries worldwide, [13][14][15][16] and CAM-use will likely continue to grow in popularity. 16 According to Swiss surveys, 25%-50% of respondents report using CAM services.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%